Survival in South Asian and White European patients after acute myocardial infarction. Issue 8 (11th February 2015) - Gholap, Nitin N; Khunti, Kamlesh; Davies, Melanie J; Bodicoat, Danielle H; Squire, Iain B
Abstract : Objective: To examine the association between ethnicity and survival following acute myocardial infarction (AMI) in White European (WE) and South Asian (SA) patients from a multiethnic UK population. Methods: Retrospective, cohort study of 4111 (N=730, 17.8% of SA ethnicity) hospitalised patients, with AMI from a tertiary coronary care centre in the UK, admitted between October 2002 and September 2008. The primary end point was all-cause mortality. The association of ethnicity with survival post AMI was assessed using the Cox regression analysis. Results: Compared with WE patients, SA patients were on average younger (62.0 years vs 67.3 years) and had higher prevalence of cardiovascular risk factors including diabetes (39.7% vs 16.1%). During follow-up (median 912, range 1–2556, days), crude mortality rate was 22.6% in SA patients and 26.0% in WE patients (p=0.061). SA ethnicity did not show univariate (HR 0.85 (0.72 to 1.01)) or multivariate (HR, 1.12 (0.94 to 1.34)) association with mortality. Findings were similar for mortality during 0–30 days (1.30 (0.99 to 1.70)), >30 days−1 year (0.97 (0.67 to 1.40)), >1 year–3 years (1.21 (0.83 to 1.76)), >3 years (0.82 (0.47 to 1.41)), and for long-term mortality in survivors from 30 days (1.02 (0.81 to 1.29)). Conclusions: When adjusted for differing prevalence of cardiovascular risk factors in the two ethnic groups, survival following AMI was similar for SA and WE patients in the UK.